Reducing mathematics anxiety among deaf learners through relaxation and rational emotive behaviour therapies: A randomised-control study - Olufemi Timothy Adigun; Oladipupo ‘W. Omobosola; Malephoto Niko Ruth Lephoto; Gideon Kwesi Obosu (International Journal of Educational Research Open)
The effects of Rational Emotive Behavioural Therapy (REBT) and Relaxation Therapy (RT) on mathematics anxiety (MA) were examined among Deaf learners (DLs) in Oyo State in Nigeria. The randomized controlled study adopted a purposive sampling procedure to select three schools for the Deaf and Deaf learners (DLs) in Oyo State. A random sampling procedure was employed to select 60 DLs who were assigned to two experimental groups REBT (n = 25; male = 10; female = 15), RT (n = 17; male = 8; female = 9), and a control group (n = 20; male = 11; female = 9). The Mathematics Anxiety Scale (MAS) was used to screen the participants. The data gathered were analysed using the analysis of variance and descriptive charts. The findings revealed the efficacy of the two therapeutic interventions in reducing MA among DLs. The estimated mean difference between the treatment and control groups showed the following: REBT (15.66), RT (11.63), and control group (9.99). This study, therefore, concluded that REBT and RT were effective at drastically reducing Deaf learners’ anxiety regarding mathematics. Appropriate recommendations were made and implications were highlighted for practice, policy, and research, based on the findings